2017
DOI: 10.3171/2015.10.jns151022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of the cortical hyperintensity belt sign in fluid-attenuated inversion recovery images after bypass surgery for moyamoya disease

Abstract: OBJECTIVE Transient neurological symptoms are frequently observed during the early postoperative period after direct bypass surgery for moyamoya disease. Abnormal signal changes in the cerebral cortex can be seen in postoperative MR images. The purpose of this study was to reveal the radiological features of the "cortical hyperintensity belt (CHB) sign" in postoperative FLAIR images and to verify its relationship to transient neurological events (TNEs) and regional cerebral blood flow (rCBF). METHODS A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 37 publications
2
61
1
Order By: Relevance
“…Six studies reported use of the ROSA robot [1318] and two the Neuromate robot [12, 19]; the other robots used were the Puma 200 robot [2], Renaissance robot [20], Minerva robot (Swiss Federal Institute of Technology of Lausanne, Switzerland) [21], MKM robot (Zeiss, Oberkochen, Germany) [22], Surgiscope robot (ISIS, Grenoble, France) [23], iSYS1 robot (iSYS, Kitzbühel, Austria) [24], and RONNA G3 robot (University of Zagreb, Croatia) [25]. The size and configuration of the reported devices varied significantly with the ROSA and Neuromate robots, occupying a large footprint and weighing up to 200 kg, and the Renaissance and iSYS1 robots being small enough to fix directly to the patient’s head and Mayfield clamp respectively, and weighing as little as 1.4 kg [20, 24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies reported use of the ROSA robot [1318] and two the Neuromate robot [12, 19]; the other robots used were the Puma 200 robot [2], Renaissance robot [20], Minerva robot (Swiss Federal Institute of Technology of Lausanne, Switzerland) [21], MKM robot (Zeiss, Oberkochen, Germany) [22], Surgiscope robot (ISIS, Grenoble, France) [23], iSYS1 robot (iSYS, Kitzbühel, Austria) [24], and RONNA G3 robot (University of Zagreb, Croatia) [25]. The size and configuration of the reported devices varied significantly with the ROSA and Neuromate robots, occupying a large footprint and weighing up to 200 kg, and the Renaissance and iSYS1 robots being small enough to fix directly to the patient’s head and Mayfield clamp respectively, and weighing as little as 1.4 kg [20, 24].…”
Section: Resultsmentioning
confidence: 99%
“…The size and configuration of the reported devices varied significantly with the ROSA and Neuromate robots, occupying a large footprint and weighing up to 200 kg, and the Renaissance and iSYS1 robots being small enough to fix directly to the patient’s head and Mayfield clamp respectively, and weighing as little as 1.4 kg [20, 24]. …”
Section: Resultsmentioning
confidence: 99%
“…28 In revascularization surgery for MMD, gray matter lesions are transiently found on conventional MRI. 13,16 Subcortical edema has also been reported, although it is not frequently found in the majority of adult patients. 33 Whether the revascularization procedure in MMD induces covert structural changes remains unclear.…”
mentioning
confidence: 99%
“…[15] The DWI and fluid attenuated inversion recovery (FLAIR) sequence could also be helpful to identify hyperperfusion and acute ischemia with typical radiological features. [15][16][17] In our case, we suspected that the transient delirium might have been associated with hyperperufusion syndrome, so we followed our previous protocol with CBF analysis and neuroimaging on the third postoperative day. However, in this case, the patient's neurological event occurred within 2 days after surgery, and the imaging beyond that time did not provide a timely evaluation for tailoring management prior to the formation of the new cerebral infarction.…”
Section: Discussionmentioning
confidence: 97%